Dietary changes during the COVID-19 lockdown in Iranian households: are we witnessing a secular trend? A narrative review - Nikooyeh, Bahareh; Ghodsi, Delaram; Amini, Maryam; Rabiei, Samira; Rasekhi, Hamid; Motlagh, Mohammad Esmaeil; Neyestani, Tirang R. (Frontiers in Public Health, 2024)
Background The COVID-19 pandemic, which emerged in late 2019, influenced nearly all aspects of human life, including food choices and dietary habits. Methodology A web-based search was conducted from March to April 2024 in MEDLINE/PubMed, CINAHL, Embase, and the Cochrane Library for published reports of large-scale surveys of dietary changes during or shortly after the coronavirus pandemic lockdown in Iran. The keywords used were coronavirus OR COVID-19, diet OR nutrition, household, and Iran. Studies that focused on specific areas, subgroups (such as students), or just one city or province were not included. To monitor dietary changes from the years before the lockdown, we used and plotted data from the Household Income and Expenditure Survey (HIES), as provided by the Statistical Center of Iran. Results The overall results of the nationwide studies conducted during the lockdown period in Iran revealed that a significant proportion of the households reduced their consumption of milk, yogurt, cheese, red meat, white meat, eggs, and rice/bread. In approximately 47% of the households where weekly consumption of animal protein sources decreased, the consumption of rice and bread increased. Accordingly, 35 and 44% of households reported a decrease in the consumption frequency of fruits and snacks, respectively. Additionally, 21% of those who reduced their fruit consumption completely removed fruits from their food basket. Meanwhile, the use of dietary supplements, especially vitamin D, vitamin C, zinc, and multivitamins, had increased in households, particularly among those with higher incomes. Decreased income was a common reason for all of these dietary changes, which can have major health consequences in the long term. Conclusion This review provides evidence that the observed changes had already begun years before the pandemic and presumably have not yet returned to the pre-pandemic situation. Finally, we suggest some strategies for policymakers to overcome the crisis and enhance community the nutrition and health of general population.